Breast-feeding in a UK urban context: Who breast-feeds, for how long and does it matter? - Wright, C.; Parkinson, K.; Scott, Jane (Cambridge University Press, 2006)
Objective: To investigate what factors relate most strongly to breast-feeding duration in order to successfully support breast-feeding mothers. Design: Prospective birth cohort study using questionnaires, routinely collected weights and health check at age 13 months. Setting: Gateshead, UK. Subjects: Parents of 923 term infants born in a defined geographical area and recruited shortly after birth, 50% of whom were breast-feeding initially. Results: Only 225 (24%) infants were still breast-fed at 6 weeks, although 136 (15%) continued beyond 4 months. Infants in the most affluent quintile were three times more likely to be initially breast-fed (P , 0.001) and five times more likely to still be feeding at 4 months (P ¼ 0.001) compared with infants in the most deprived quintile. A third of breast-fed infants were given supplementary feeds in the maternity unit and this was associated with a 10-fold increase in odds of giving up breast-feeding by discharge (P ¼ 0.001). Frequent feeding was reported as a reason for giving up in 70% of mothers at 6 weeks and 55% at 4 months. Those infants who stopped breastfeeding earliest showed the most rapid weight gain and were tallest at age 13 months. Non-breast-fed infants had 50% more family doctor contacts up to age 4 months (P ¼ 0.005). Conclusions: Initiation of breast-feeding in urban Britain remains strongly determined by socio-economic background and early cessation seems to be related to frequent feeding and rapid growth as well as a continuing failure to eradicate health practices that undermine breast-feeding. Those infants not receiving breast milk suffered increased morbidity, but the apparent association between breast-feeding duration and growth probably reflects reverse causation.